Answer:
The rule which represent the function as shown in the table is:
![f(n)=3n](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d6ad6bpm7rjm2ikj8tza297fk3oqcx9vax.png)
Explanation:
We are given a table as follows:
x 2 -1 0
y 6 -3 0
Now we are asked to find the function which represent these table of values.
a)
![f(n)=n+3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yksjhsmcvkl0d6nu60dp8gcdg3kuheosxx.png)
Here x is represented by n and y by f(n)
when n=2 we must have f(n)=6
Hence, we put n=2 in the given expression and check,
![f(2)=2+3=5\\eq 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4bnlejwlfdxdrdchlhwlw9zx7bwm5ye02f.png)
Hence, this is not a correct function.
b)
![f(n)=(1)/(3)n](https://img.qammunity.org/2020/formulas/mathematics/middle-school/662dv6jeude53u9pt1sugmlyeib5m58uo5.png)
Again we check for n=2
We have:
![f(2)=(1)/(3)* 2=(2)/(3)\\eq 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nvexciueh0r4qm8d9fhrl141zdtv8nkoyt.png)
Hence, it is not a correct expression.
So we are left with option: c)
c)
![f(n)=3n](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d6ad6bpm7rjm2ikj8tza297fk3oqcx9vax.png)
By putting the value of n=2,-1 and 0
we see that the expression matches the table of values.
( since,
when n=2 we have:
![f(2)=3* 2=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2v0f02srufw25f7x7jiu3al61ldpazzkbo.png)
when n= -1 we have:
![f(-1)=3* -1=-3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8x9vsgdj00sndgwqi9b1b72li5lckjypfg.png)
and when n=0 we have:
)
Hence, this is a correct expression.